2003
DOI: 10.1029/2003jb002394
|View full text |Cite
|
Sign up to set email alerts
|

Active fault creep variations at Chihshang, Taiwan, revealed by creep meter monitoring, 1998–2001

Abstract: [1] The daily creep meter data recorded at Chihshang in 1998-2001 are presented. The Chihshang creep meter experiment was set up across the Chihshang thrust fault, the most active segment of the Longitudinal Valley Fault, which is the present-day plate suture between the Eurasian and the Philippine Sea plates in eastern Taiwan. Near-continuous data recording at two sites revealed different surface fault motions yet similar annual shortening rates: 16.2 mm at the Tapo site (comprising two connected creep meters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
129
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 102 publications
(137 citation statements)
references
References 21 publications
7
129
0
1
Order By: Relevance
“…The Coastal Range is attached to and thrust over the late Quaternary alluvial deposits of the Longitudinal Valley along the LVF. The earthquakes distribution and focal mechanisms indicate that the average fault plane strike of the central-southern part of the LVF is N20° -25°E with a listric-shaped dip of 25° -70° (Lee et al 2003;Kuochen et al 2004;Lee et al 2006). The seismicity from Hualien to Taitung in Eastern Taiwan can be grouped into north and south portions, separated near the middle of the Coastal Range.…”
Section: Geological Settingmentioning
confidence: 96%
See 1 more Smart Citation
“…The Coastal Range is attached to and thrust over the late Quaternary alluvial deposits of the Longitudinal Valley along the LVF. The earthquakes distribution and focal mechanisms indicate that the average fault plane strike of the central-southern part of the LVF is N20° -25°E with a listric-shaped dip of 25° -70° (Lee et al 2003;Kuochen et al 2004;Lee et al 2006). The seismicity from Hualien to Taitung in Eastern Taiwan can be grouped into north and south portions, separated near the middle of the Coastal Range.…”
Section: Geological Settingmentioning
confidence: 96%
“…The 180-km-long Longitudinal Valley in Eastern Taiwan represents the plate suture along which active left-lateral oblique thrusting of the Longitudinal Valley Fault (LVF in Fig. 1a) accommodates the present surface horizontal shortening of 2 -3 cm yr -1 , which is about one-third of the 8.2 cm yr -1 tectonic contraction across the whole Taiwan mountain belt (Biq 1965;Ho 1986;Yu et al 1990; Lee and Angelier 1993;Angelier et al 1997;Yu et al 1997;Lee et al 2003). On the northern and southern tips of the NNE-trending Taiwan mountain belt, the Ilan and Pingtung plains, show both lateral tectonic escape and/or horizontal strata bending with a rather complex combination of deformation features, such as block rotation, strike-slip faulting (i.e., shearing) and normal faulting (i.e., extension) (Angelier et al 1990;Lu et al 1995;Rau et al 2008;Angelier et al 2009;Ching et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Horizontal velocity field derived from the GPS measurements indicated a distinct discontinuity across the LVF with a difference of velocity of about 30 mm/yr (Yu and Kuo, 2001). This horizontal shortening is principally revealed by shallow aseismic slips on the LVF (Yu and Liu, 1989;Yu et al, 1990;Lee et al, 2003). The creeping behavior of the LVF is prominent, especially in its southern part from Juisui to Taitung (Fig.…”
Section: Geodetic Measurements In the Longitudinal Valley Areamentioning
confidence: 96%
“…During the past decades, scientists have carried out a variety of quantitative and qualitative analyses to better understand the processes of the plate suture zone in this arc-continent collision (Hsu, 1962;Barrier et al, 1982;Ho, 1986;Yu and Liu, 1989;Yu et al, 1992;Lee and Angelier, 1993;Angelier et al, 1997;Lee et al, 1998;Hu et al, 2001;Yu and Kuo, 2001;Shyu et al, 2008). Efforts from previous studies indicated a rapid shortening of about 30 mm/year in the middle and southern segments of the Longitudinal Valley Fault (LVF), which is the major fault of the plate suture in the valley (Yu et al, 1992;Yu and Kuo, 2001;Lee et al, 2003). However, a more complex architecture of the fault system and tectonic context with at least two branches (i.e., the Luyeh fault to the west and the Lichi fault to the east) and a few secondary strike-slip faults have been reported in the southern end of the LVF ( Fig.…”
Section: Introductionmentioning
confidence: 99%